2023
DOI: 10.1111/1556-4029.15229
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an odor permeable membrane device for the storage of explosives and use as canine training aids

Abstract: The storage and use of explosives is regulated at the state and federal level, with a particular focus on physical security and rigorous accounting of the explosive inventory. For those working with explosives for the training and testing of explosive‐detecting canines, cross‐contamination is an important concern. Hence, explosives intended for use with canine teams must be placed into secondary storage containers that are new, clean, and airtight. A variety of containers meet these requirements and include sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Safety fuse was also analyzed and confirmed in a previous study, with the most prominent volatile being sulfur, which is a component of the black powder filling in the fuse [14] (Figure 5).…”
Section: Initiatorssupporting
confidence: 71%
“…Safety fuse was also analyzed and confirmed in a previous study, with the most prominent volatile being sulfur, which is a component of the black powder filling in the fuse [14] (Figure 5).…”
Section: Initiatorssupporting
confidence: 71%
“…The device has been tested for safe containment of hazardous components passing drop, altitude, high and low temperatures, vibration, and crush tests (unpublished data). Tests have shown that volatile compounds from the material within the TADD are freely able to pass through the membrane for detection in the headspace without any physical material escaping or contaminating the outside of the device [6, 7]. Previous research has tested explosive‐related volatile organic compounds (VOCs) through the membrane to include nitromethane, toluene, nitromethane, 1‐nitropropane, and r‐limonene, and found that these compounds readily evaporated from the TADD with and without the membrane, though the presence of the TADD membrane decreased the flux of the vaporous components by several odors of magnitude [7].…”
Section: Introductionmentioning
confidence: 99%